A graphene oxide scaffold-encapsulated microcapsule for polysulfide-immobilized long life lithium–sulfur batteries. Issue 11 (11th May 2022) - Lin, Xirong; Yang, Chaoyu; Han, Tianli; Li, Jinjin; Chen, Zhonghua; Zhang, Haikuo; Mu, Kai; Si, Ting; Liu, Jinyun
Abstract : A three-dimensional graphene oxide scaffold/sulfur composite-encapsulated microcapsule for lithium–sulfur batteries is developed through a microfluidic approach, which displays high electrochemical performance. Abstract : Engineering high-performance cathodes for high energy-density lithium–sulfur (Li–S) batteries is quite significant to achieve commercialization. Here, we develop a graphene oxide scaffold/sulfur composite-encapsulated microcapsule (GSM) for high-performance Li–S batteries, which is prepared through the co-flow focusing (CFF) approach. The GSM-based cathode displays a high capacity of 1004 mA h g −1 at 0.2C after cycling 200 times, a long-term cycling stability after 1000 cycles at 2C, and a good rate-performance. At temperatures of −5 °C and 45 °C, the electrochemical performance is also excellent. The computational calculations based on density functional theory (DFT) verify the high adsorption energies of the microcapsules towards polysulfides, suppressing the shuttle effect efficiently. It is expected that the GSM system developed based on the CFF method here and its high electrochemical performance will enable it to be applicable for preparing many other emerging energy-storage materials and secondary batteries.